The growth and nutritional quality of the African eggplant under abiotic stress - David-Rogeat, Noémie (2024)
The African eggplant (Solanum aethiopicum L.), a popular indigenous vegetable, is well-suited to local environments, highly nutritious, and has lower water and fertiliser requirements than its close Solanum relatives such as the brinjal eggplant or tomato. It might offer a solution to the growing threat of food insecurity arising from the increasing frequency and severity of environmental stresses worldwide, particularly in Africa. However, research on the African eggplant’s tolerance to abiotic stress is lacking, limiting its full potential.